Basic Insights into Tunable Graphene Hydrogenation - Schäfer, Ricarda; Dasler, Daniela; Mundloch, Udo; Hauke, Frank; Hirsch, Andreas (Journal of the American Chemical Society, 2016)
The hydrogenation and deuteration of graphite with potassium intercalation compounds as starting materials were investigated in depth. Characterization of the reaction products (hydrogenated and deuterated graphene) was carried out by thermogravimetric analysis coupled with mass spectrometry (TG-MS) and statistical Raman spectroscopy (SRS) and microscopy (SRM). The results reveal that the choice of the hydrogen/deuterium source, the nature of the graphite (used as starting material), the potassium concentration in the intercalation compound, and the choice of the solvent have a great impact on the reaction outcome. Furthermore, it was possible to prove that both mono- and few-layer hydrogenated/deuterated graphene can be produced.

Direct Covalent Coupling of Porphyrins to Graphene - Dasler, Daniela; Schäfer, Ricarda; Minameyer, Martin; Hitzenberger, Jakob; Hauke, Frank; Drewello, Thomas; Hirsch, Andreas (Journal of the American Chemical Society, 2017)

Mono- and Ditopic Bisfunctionalization of Graphene - Knirsch, Kathrin; Schäfer, Ricarda; Hauke, Frank; Hirsch, Andreas (Angewandte Chemie International Edition, 2016)
For the first time, the bisfunctionalization of graphene by employing two successive reduction and covalent bond forming steps is reported. Bulk functionalization in dispersion and functionalization of individual sheets deposited on surfaces have both been carried out. Whereas in the former case attacks from both sides of the basal plane are possible and can lead to strain-free architectures, in the latter case, retrofunctionalizations can become important when the corresponding anion of the addend is a sufficiently good leaving group.
Keywords: functionalization; graphene; Raman spectroscopy; retrofunctionalization; topicity

Novel λ(3)-iodane-based functionalization of synthetic carbon allotropes (SCAs)-common concepts and quantification of the degree of addition - Hof, Ferdinand; Schäfer, Ricarda; Weiß, Cornelius; Hauke, Frank; Hirsch, Andreas (Chemistry - A European Journal, 2014)
The covalent functionalization of carbon allotropes represents a main topic in the growing field of nano materials. However, the development of functional architectures is impeded by the intrinsic polydispersibility of the respective starting material, the unequivocal characterization of the introduced functional moieties, and the exact determination of the degree of functionalization. Based on a novel carbon allotrope functionalization reaction, utilizing lambda(3)-iodanes as radical precursor systems, we were able to demonstrate the feasibility to separate and to quantify thermally detached functional groups, formerly covalently linked to carbon nanotubes and graphene through thermogravimetric GC-MS.
Keywords: analytical chemistry; carbon allotropes; graphene; hypervalent iodine; nanotubes

On the way to graphane - Pronounced fluorescence of polyhydrogenated graphene - Schäfer, Ricarda; Englert, Jan; Wehrfritz, Peter; Bauer, Walter; Hauke, Frank; Seyller, Thomas; Hirsch, Andreas (Angewandte Chemie International Edition, 2013)
Chemistry meets graphane: A Birch-type reaction using frozen water as a gentle proton source causes the exfoliation of graphite and formation of hydrogenated graphene with electronically decoupled π-nanodomains. This highly functionalized graphene displays pronounced fluorescence. Copyright © 2013 WILEY-VCH Verlag GmbH & Co. KGaA, Weinhei
Keywords: carbon allotropes; fluorescence; graphane; graphene; hydrogenation

Polyhydrogenated Graphene: Excited State Dynamics in Photo- and Electroactive Two-Dimensional Domains - Strauß, Volker; Schäfer, Ricarda; Hauke, Frank; Hirsch, Andreas; Guldi, Dirk Michael (Journal of the American Chemical Society, 2015)
Understanding the phenomenon of intense photoluminescence in carbon materials such as hydrogenated graphene, graphene nanoribbons, and so forth is at the forefront of investigations. In this study, six different types of hydrogenated graphene (phG) produced from different starting materials were fully characterized in terms of structure and optical spectroscopy. Comprehensive photoluminescence lifetime analyses of phGs were conducted by combining time-correlated single-photon counting with steady-state fluorescence spectroscopy and femtosecond transient absorption spectroscopy. The conclusion drawn from these assays is that graphene islands with diameters in the range from 1.1 to 1.75 nm reveal band gap photoluminescence between 450 and 800 nm. As a complement, phGs were implemented in hybrids with water-soluble electron accepting perylenediimides (PDIs). By virtue of mutual π-stacking and charge transfer interactions with graphene islands, PDIs assisted in stabilizing aqueous dispersion of phG. Implicit in these ground state interactions is the formation of 300 ps lived charge separated states once photoexcited.

Scanning-Raman-microscopy for the statistical analysis of covalently functionalized graphene - Englert, Jan; Vecera, Philipp; Knirsch, Kathrin; Schäfer, Ricarda; Hauke, Frank; Hirsch, Andreas; Hauke, Frank (Acs Nano, 2013)
We report on the introduction of a systematic method for the quantitative and reliable characterization of covalently functionalized graphene based on Scanning-Raman-Microscopy (SRM). This allows for recording and analyzing several thousands of Raman spectra per sample and straightforward display of various Raman properties and their correlations with each other in histograms or coded 2D-plots. In this way, information about the functionalization efficiency of a given reaction, the reproducibility of the statistical analysis, and the sample homogeneity can be easily deduced. Based on geometric considerations, we were also able to provide, for the first time, a correlation between the mean defect distance of densely packed point defects and the Raman I/I ratio directly obtained from the statistical analysis. This proved to be the prerequisite for determining the degree of functionalization, termed θ. As model compounds, we have studied a series of arylated graphenes (GPh) for which we have developed new synthetic procedures. Both graphite and graphene grown by chemical vapor deposition (CVD) were used as starting materials. The best route toward GPh consisted of the initial reduction of graphite with a Na/K alloy in 1,2-dimethoxyethane (DME) as it yields the highest overall homogeneity of products reflected in the widths of the Raman I /I histograms. The Raman results correlate nicely with parallel thermogravimetric analysis (TGA) coupled with mass spectrometry (MS) studies. © 2013 American Chemical Society.

Substrate-Modulated Reductive Graphene Functionalization - Schäfer, Ricarda; Weber, Konstantin; Kolesnik-Gray, Maria; Hauke, Frank; Krstic, Vojislav; Meyer, Bernd; Hirsch, Andreas (Angewandte Chemie International Edition, 2016)
Covalently functionalizing mechanical exfoliated mono- and bilayer graphenides with λ-iodanes led to the discovery that the monolayers supported on a SiO2 substrate are considerably more reactive than bilayers as demonstrated by statistical Raman spectroscopy/microscopy. Supported by DFT calculations we show that ditopic addend binding leads to much more stable products than the corresponding monotopic reactions as a result of the much lower lattice strain of the reactions products. The chemical nature of the substrate (graphene versus SiO2) plays a crucial rol
Keywords: functionalised grapnene; substrate interactions; chemical reactivity